The role of diet in the overlap between gastroesophageal reflux disease and functional dyspepsia - Chirila, Ioan; Morariu, Ionela Daniela; Bogdana Barboi, Oana; Drug, Vasile Liviu (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The prevalence of functional dyspepsia partially overlaps with gastroesophageal reflux disease (GERD), and this suggests common pathogenic mechanisms. The role of diet in these conditions is still under investigation. The present study evaluated the type of diet associated with functional dyspepsia and GERD. Materials and Methods: A representative sample of subjects was invited to the family doctors’ office, and an interview-based questionnaire was administered to diagnose functional dyspepsia and GERD (using Rome III and Montreal criteria, respectively) and to evaluate eating habits and the frequency of food intake. Correlation and regressions were used for statistical analyses, and the results were presented as odds ratio and 95% confidence interval. Results: In total, 184 subjects participated in a 4-month study. Functional dyspepsia was present in 7.6%, and GERD was present in 31.0%. The predictors for dyspepsia were low educational level (22.4, 3.3–150.1, p=0.001), consumption of canned food, and the use of alcoholic drinks at least weekly. The predictors for GERD were advanced age and the use of canned food (13.9, 3.6–53.9, p<0.001) or fast food (4.6, 1.7–12.1, p=0.002). Conclusion: This study provides new data on the overlap of GERD and functional dyspepsia and reveals that these disorders may be associated with the consumption of canned food, fast food, and alcoholic beverages.